Clinical case reports - V. B. Filimonov; R. V. Vasin; S. V. Snegur; V. N. Panchenko (Исследования и практика в медицине)
Echinococcosis is a severe parasitic disease with a fecal-oral mechanism of the pathogen transmission. It caused by the introduction into the organism and development in the body of the larval stage of tapeworm of the genus Echinococcus, with the formation of parasitic cysts in the liver, lungs, kidneys and other organs. Kidney echinococcosis ranks seventh in frequency after echinococcosis of the liver, lungs, peritoneum, omentum, muscles, spleen, and ranges from 1.5 to 5% relative to echinococcal lesions of other organs. It is necessary to use data from the epidemiological history, determination of blood antibodies to echinococcus by enzyme immunoassay, ultrasonography of the kidneys and the abdominal cavity, radiography of the lungs, review and excretory urography, nephroscintigraphy, x-ray computer and magnetic resonance imaging for the diagnostics of kidney echinococcosis. The article presents a clinical case of theechinococcal lesion in the left patient's kidney. The final diagnosis was made during the operation (left nephrectomy). It indicates some difficulty of diagnostics of this disease. Antiparasitic chemotherapy was performed in the postoperative period. Subsequent dynamic observation of the patient revealed no recurrence of echinococcosis.